The Role of Digital Innovation (AI, IoT, and Big Data) in Accelerating Circular Economy Business Models in the Creative Industries: A Systematic Literature Review - Ni Made Ria Kurniasih Astuty (Eduvest - Journal of Universal Studies, 2026)
This study investigates the role of digital innovation, specifically Artificial Intelligence (AI), the Internet of Things (IoT), and big data, in accelerating the adoption of circular economy business models within the creative industries. Using a Systematic Literature Review (SLR) guided by PRISMA 2020, 26 empirical and conceptual studies published between 2020 and 2025 were analyzed across the fashion, textile, and design subsectors. The findings reveal that IoT is the most frequently implemented technology, primarily enabling real-time tracking, life cycle monitoring, and resource optimization. Big data analytics supports evidence-based decision-making and predictive modeling for waste reduction and efficient logistics, while AI contributes to intelligent sorting, demand forecasting, and digital servitization for circular business model innovation. Collectively, these technologies foster transparency, automation, and collaboration, allowing creative firms to close material loops, extend product life cycles, and enhance traceability. The results highlight that the integration of digital tools creates synergistic ecosystems that embed sustainability into creative production and consumption. However, disparities in digital readiness, financial capacity, and regulatory frameworks continue to constrain large-scale adoption, particularly among small and medium enterprises. Theoretically, this research advances understanding of digital circularity as a strategic interface between technological innovation and sustainable transformation, contributing a conceptual synthesis that links digital capabilities with circular economy mechanisms in creative sectors. The study concludes that future research should explore cross-sectoral governance, data standardization, and the sociocultural dimensions of digital sustainability to strengthen the systemic transition toward regenerative creative economies.